Enhanced dielectric properties and band gap expansion in NiO submicron powders via substitutional be doping - Dongpyo Hong; Gyung Hyun Kim; Eun Jung Lee; Young Il Moon; Ok Sung Jeon; Se Hun Lee; Sang-Hwa Lee; Young Jun Yoo; Sang Yoon Park (Materials Research Express)
The fundamental tradeoff has made it difficult to enhance the low permittivity of wide bandgap semiconductors without sacrificing the bandgap. In this work we demonstrate that high-concentration substitutional Be doping can enhance NiO’s dielectric properties and simultaneously widen the bandgap. Up to 5 at% of Ni in NiO could be substituted by Be while maintaining the rocksalt crystalline structure. The real part of permittivity at low frequencies was found to be significantly increases (40%) while bandgap also increases from 3.06 to 3.37. These findings offer engineering insights for developing high-K wide bandgap materials, essential for various electronic and optoelectronic applications.